Microbiological quality, fungal diversity and aflatoxins contamination in carob flour (Prosopis flexuosa) - Mom, María Pía; Romero, Stella Maris; Larumbe, Ada Gabriela; Iannone, Leopoldo; Comerio, Ricardo Mario; Santana Smersu, Camila Soledad; Simón, Mariano; Vaamonde, Graciela (Elsevier, 2020)
Carob flour is obtained from pods of some species of Prosopis, leguminous trees that abound in many desert habitats worldwide. Currently, this product is available in healthy food stores in several countries, including Argentina, as a nontraditional meal of growing interest with multiple applications for the preparation of puddings, biscuits and snacks, among others. The objective of the present study was to evaluate the microbial quality of carob flour on basis of the presence of deteriorative and pathogenic microorganisms. Fungal diversity of the mycobiota was also studied with a special interest in toxigenic fungi. Eighteen samples of carob flour (Prosopis flexuosa) were analysed. Standard plate count of aerobic mesophilic bacteria showed levels of contamination ranging from <102 (estimative) to 6.8 × 105 CFU/g; total coliforms from <102 (estimative) to 4.7 × 105 CFU/g; moulds and yeasts from 2.1 × 102 to 8.1 × 104. In all samples, the absence of Salmonella sp. was verified in 25 g and counts of Bacillus cereus less than 102 were observed. These results indicate that from the safety point of view the carob flour studied does not have a significant microbial load. Regarding to fungal contamination, Aspergillus and Penicillium were the genera more diverse in species and were present in all the samples. Some of the species identified were potential mycotoxins producers. Among the most frequently detected species in the studied mycobiota were the Aspergillus of the Flavi section, well recognized as potential aflatoxin producers. The A. flavus species was one of the most widely distributed, since it was detected in almost all samples. A. parasiticus and A. arachidicola were found more sporadically. Aflatoxins analysis demonstrated that a high proportion of the samples were contaminated with aflatoxins in concentrations relatively low, ranging from 1.26 to 20.33 μg/kg of total aflatoxins. Type G aflatoxins are much less frequent contaminants than type B aflatoxins, which is consistent with the fact that A. parasiticus and A. arachidicola (producers of type B and G aflatoxins) were detected sporadically, while A. flavus, which produces aflatoxins B1 and B2, was present in a high number of samples. Results of the present work indicate that carob flour is susceptible to Aspergillus section Flavi and aflatoxin contamination and should be subjected to aflatoxin monitoring prior to marketing as required for other traditional crops.